A specification model for temporal and spatial relations of segments in multimedia presentations - Hakkoymaz, V. (Journal of Digital Information Management, 2010)
In this paper, we introduce a conceptual tuplebased model for specification of spatial, temporal and semantic relationships among media segments in a multimedia presentation. A multimedia presentation contains various kinds of multimedia objects such as audio, video, images, text media types and so on. The organization of a presentation is a complex task in that the display order of presentation content (in time and space) must be specified. The critical decisions for presentation construction include content selection, content organization, and content delivery. Once the decision is made on the organization of the content of the presentation, it must be conveyed to the end user in the correct organizational order and in a timely fashion. Assuming that a set of multimedia segments gets organized into a presentation graph, this conceptual model formalizes a complete presentation using event-points for these segments. Three possible end-user environments of multimedia presentation are considered for presentation playout as (i) the one without any constraint, (ii) another one with a single constraint, and (iii) the third one with multiple constraints (one constraint for each type of multimedia segments in the organized presentation). In accordance with these limitations (i.e., without violating any of the end-user specified constraints), we give three methods for constructed presentations to be presented at the presentation terminal.
Keywords: Bayesian information criterion (BIC); Document clustering; Document retrieval; Dynamic clustering; Performance; Termination criterion